Value conflicts implicit in the educational roles, tasks and functions of the training and development practitioner in South Africa - Gamble, Jeanne Isobel (Department of Philosophy, 2026)
The presented dissertation focusses on a 'particular occupational grouping, namely the · training and development specialists employed by large organisations that exist specifically as profit-making , enterprises. It examines the functions of a corporate training department and the related roles which trainers adopt in the conception and execution of their training tasks. The argument of the dissertation is that the training process is essentially a management process. The use of the term 'management' does not imply co-ordination of the work efforts of other people as in the standard definition of management, but rather the management of the range of meanings that the corporation provides to employees to persuade them that their most significant life experience exists within the corporation or an extended form of the corporation. Training and development practitioners are positioned and equipped to make resources available for the construction of such meanings. Absolute demands for productivity, efficiency and effectiveness are re-located in different discourses, which provide c:Ufferent kinds of potent~ meanings for the formation of a work identity. The aims and conclusions of the study are directed towards a historical understanding .of the consciousness and agency of training and development practitioners that allew them to internalize the conflicts which they experience in their work to make possible for them the reconciliation of the contradiction posed by John Ruskin in the nineteenth century: Observe you 'are put to a s~rn choice in this matter. You muat either mate a tool of the creature, or a man or him. You cannot make both. Men were not intended to work with the accuracy or tools, to be precise and perfect in all their actiona. Ir you will have that precision out or them, and make their ftnpn measure degreee like cog-wheels, and their arma strike cunee like aompa1111•, you muat inhumanize them. All the energy of their spirit.a muat be given to make cop and compa■■• ot thema,elvee ... On the other hand, if you will make a man or the working creature, you cannot make a tool. Let him but begin to imagiM, to *hink, to try to do anything worth doing; and the engine-tuned precision • loet at once. Out come all hia rougbneu, all bis dullneu, all bia incapability; shame upon shame, failure upon failure, pause after pause: but out comes the whole majesty of him alao .•. John Ruskin: The Stona ofVeni.ce